Exploring the Effect of Ti on Mechanical and Tribological Properties of an AlCrFe2Ni2Tix High-Entropy Alloy - Yajuan Shi; Yudong Guo; Yi Wang (Metals)
Low friction and wear constitute a challenge for metallic materials under dry sliding conditions. In the current study, we successfully prepared an AlCrFe2Ni2Tix (x = 0, 0.2, 0.4, 0.6, 0.8, 1.0) high-entropy alloy (HEA) consisting of a body-centered cubic (BCC) phase and an AlNi2Ti phase that exhibited an outstanding combination of a compression strength of above 3 GPa and a ductility degree of 26% at room temperature. Under a 20 N load, the dry friction tests showed that AlCrFe2Ni2Ti0.4 HEA had the lowest wear volume (1.498 mm3), with a coefficient of friction of 0.3929. It is related to the volume fraction of AlNi2Ti precipitate increasing with increasing Ti content, thus resulting in better wear resistance. Through the strengthening mechanism analysis, it is crucial to manipulate the composition of the AlNi2Ti precipitate to obtain desirable mechanical properties in the AlCrFe2Ni2Tix HEA. The main mechanism of wear friction is identified as adhesion wear. Therefore, the addition of Ti into AlCrFe2Ni2 HEA can effectively improve its mechanical and wear resistance due to the significant improvement in hardness and its inherent solution strengthening. Our study provides a new strategy for designing new BCC HEAs with a combination of high hardness, yield strength, and excellent wear.